The representation of George Town Heritage: A two-space analysis of local alienation - Merican, A.M. (Universiti Putra Malaysia, 2018)
This article examines the representation of George Town Heritage within the context of George Town Heritage sites, and the annual George Town Festival (GTF). It explores the heritage sites of the various communities in Penang, Malaysia. It argues beyond the Eurocentric hegemony and representations of Penang history anchored on the British occupation of the island in 1786. There also exist other levels of hegemony and various forms of representations of the heritage in Penang. This is expressed by the narratives/historical representations of various settler communities such as the Chinese, Chinese Peranakans, Indian Muslims and the Eurasians. To showcase the manifestations of these various levels of representations of heritage, the paper adopts the method of combining historiography, participant observation and document study. The article applies Hall's (1997) notion of representation as its theoretical framework. Halls's theory articulates the asymmetry between the dominant discourse and the local discourse of Penang heritage. This asymmetry reveals absence, and alienation of certain local narratives of historical relevance. The paper interrogates the following: What sort of historical consciousness do the two-spaces of analysis espouse regarding the history of Penang? What are the historical imbalances and omissions in the representation of George Town Heritage? How can the local/oral history serve as a prognosis to the historical imbalance in the narration and depiction of the history/heritage of Penang? The paper recommends the need for the GTF, and George Town Heritage Sites to commemorate the historical journey that emerged in Penang before 1786. Â© Universiti Putra Malaysia Press.